Pengaruh Kompetensi Digital, Pelatihan Kerja, dan Motivasi Terhadap Kinerja Pegawai di Lingkungan Dinas PPKUKM DKI Jakarta - Marda Ermawati; Setyo Riyanto (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2026)
This study analyzes the effects of digital competence, job training, and motivation on employee performance at the DKI Jakarta Office of Industry, Trade, Cooperatives, Small and Medium Enterprises (Dinas PPKUKM). The study was motivated by the need to strengthen human resource quality in public organizations facing digital transformation and increasingly demanding public services. A quantitative causal design was applied. The population consisted of 330 civil servants, while 181 respondents were determined using the Slovin formula at a 5% margin of error and reached through convenience sampling. Primary data were collected using a Likert-scale questionnaire and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS. The findings show that digital competence has a positive and significant effect on employee performance with a path coefficient of 0.524, job training has a positive and significant effect with a coefficient of 0.420, and motivation has a positive and significant effect with a coefficient of 0.458. The model explains 66.8% of the variance in employee performance and demonstrates good predictive relevance. Digital competence provides the largest contribution among the predictors. These findings highlight the importance of strengthening digital competence, providing job-relevant training, and sustaining employee motivation as integrated human resource development priorities for improving performance effectiveness in the public sector.